A new slurry bubble column reactor for diesel fuel. (29th September 2015) - Gidaspow, Dimitri; He, Yuting; Chandra, Vishak
Abstract: Multiphase CFD simulations have shown how to design reactors using Fischer–Tropsch chemistry. The new design uses large catalyst particles to eliminate large bubbles, has no cooling tube bundles and produces up to 50, 000 bbl/day of Diesel fuel in a 7 m diameter, 12 m high reactor at a pressure of 3 MPa and a temperature of 530 K. Graphical abstract: Highlights: A multiphase CFD model was used to design a new Fischer–Tropsch reactor. Catalyst, liquid and gas volume fractions agree qualitatively with experiments. The new reactor has no cooling tubes and is therefore less expensive. The use of large catalyst particles leads to greatly increased Diesel fuel production. Multiple jet inlets allow operation in the turbulent flow regime.